2017
DOI: 10.18203/2349-3933.ijam20174639
|View full text |Cite
|
Sign up to set email alerts
|

Study of serum lipid profile in type 2 diabetes mellitus patients and its association with diabetic nephropathy

Abstract: Background: Dyslipidaemia is highly prevalent in type 2 Diabetes mellitus patients. The role of dyslipidaemia in macrovascular complications of Diabetes have been extensively studied but its role in microvascular complications namely nephropathy is still unclear. The present study was undertaken to study the prevalence and pattern of dyslipidaemia and its association with Diabetic nephropathy (DN) in patients with type 2 DM.Methods: 100 patients with type 2 DM attending OPD or admitted, over a period of 1 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…Most of this excess risk is associated with an augmented prevalence of well-known risk factors such as hypertension, dyslipidaemia, and obesity in these patients [27]. Persistent dyslipidaemia shown in our work was collaborated by some other workers [28,29]. The characteristic features of diabetic dyslipidemia are high plasma triglyceride concentration, reduced HDL-C concentration, and increased concentration of LDL-C particles.…”
Section: Discussionsupporting
confidence: 69%
“…Most of this excess risk is associated with an augmented prevalence of well-known risk factors such as hypertension, dyslipidaemia, and obesity in these patients [27]. Persistent dyslipidaemia shown in our work was collaborated by some other workers [28,29]. The characteristic features of diabetic dyslipidemia are high plasma triglyceride concentration, reduced HDL-C concentration, and increased concentration of LDL-C particles.…”
Section: Discussionsupporting
confidence: 69%
“…The prevalence of dyslipidemia in the present study was found as 86.9% which was coinciding with other studies done by Kolhar U et al, Pandya H et al, Tagoe DN et al, and Jayarama N et al, which showed prevalence of 90%,85%, 93%, and 91% respectively. 5,[11][12][13] Insulin resistance, relative insulin deficiency and obesity are found to be associated with dyslipidemia in type 2 diabetes mellitus. 9 In the present study the hypercholesterolemia was reported as 58.6%, hypertriglyceridemia was 36.9%, increased LDL was 65.2% and lower HDL was 93.4%.…”
Section: Discussionmentioning
confidence: 99%
“…4 Diabetes mellitus is an important risk factor for cardiovascular disease and atherosclerosis as it is a common secondary cause of hyperlipidemia when the glycemic control is poor. 5 The prevalence of dyslipidemia in type 2 diabetes is double with respect to the general population. 6 Approximately 80% of deaths in patients with diabetes are prone to coronary vascular diseases and the Asian Indians have high risk of coronary heart disease than whites.…”
Section: Introductionmentioning
confidence: 99%
“…Various other studies also supported that the duration of disease is associated with the altered lipid profile with duration of disease in type 2 diabetes mellitus patients [6,7] . Numerous studies also indicated very high level of serum total cholesterol, serum triglyceride, LDL-cholesterol and VLDLcholesterol but no significant increase in HDLcholesterols [8][9][10] . Otamere H.O., 2011and Nyasatu et al, 2017 indicated that the duration of disease was not associated with altered lipid profile which is against our study [11,12] .…”
Section: Discussionmentioning
confidence: 99%